A comparative study of the efficacy of instrument-assisted soft tissue mobilization and massage techniques in patients with patellofemoral joint pain - Liu, Yang; Wang, Yidan (Frontiers in Medicine, 2023)
Purpose: The aim of this study was to compare the clinical efficacy of instrument-assisted soft tissue mobilisation (IASTM) and manipulative therapy Tui-na techniques in the treatment of patients with patellofemoral joint pain syndrome, and to evaluate their impact on pain relief, functional improvement, and joint range of motion. Results: There was no significant difference in the basic information of the two intervention groups (p>0. 05). After the first treatment and four weeks of treatment, the Lysholm score in both groups significantly improved (p<0. 05), indicating that both interventions can improve the function of patients' lower limbs. However, the Lysholm score in the IASTM group significantly increased compared with that of the massage group after four weeks of treatment, indicating that its improvement in functional performance is superior. Both groups showed significant improvement in knee joint pain after the first treatment and four weeks of treatment (p<0. 05), with the IASTM group having a lower VAS score and better pain improvement after four weeks of treatment. The strength of the two intervention groups significantly increased after the maximum isometric muscle strength test of the lower limb extensor muscles before and after four weeks of treatment (p<0. 05). After the MTT test, the extension angle, deviation angle, and hip abduction angle of the tested legs in the two intervention groups were significantly reduced (p<0. 001), indicating an improvement in lower limb joint mobility. Conclusion: IASTM treatment and Tui-na manipulation therapy significantly reduced pain, improved knee flexibility and increased range of motion of the lower extremity in patients with PFPS. However, IASTM treatment significantly improved pain and function and sustained pain in the short to medium-term post-trial period.